PENERAPAN MODEL PEMBELAJARAN DISCOVERYLEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SEJARAH INDONESIA KELAS X OTKP 1 SMK NEGERI 1DUKUHTURI TAHUN PELAJARAN 2021/2022 - Ahmad Faizal Bakhtiar (Historia Pedagogia, 2024)
This research aims to improve the learning outcomes of 1st degree Otkp At SMK Negeri 1 Dukuhturi. The research results show that through the application of the Discovery Learning model it is possible improve learning outcomes in Indonesian History subjects for class X students at SMK Negeri 1 Dukuhturi Tegal Regency odd semester 2021/2022 academic year with the percentage of students who complete (qualified the Passing Grade) from the initial conditions (pre-cycle) compared to the cycle I experienced increased from 40% to 63% while in cycle II it had increased to 83%, and in cycle III increased again to 98%. Likewise from the initial conditions (pre-cycle) to the conditions At the end (cycle II) the percentage of students who had completed (qualified the Passing Grade) had increased by 43%.